Attitudes of Tourism Business Actors After the Poso Conflict - Vanda L.A. Pombadju; Angel M. Parirak; Donnye R. Amping; Melda Limaheluw; Sutarto Wijono (International Journal Labs, 2023)
The indonesian state has so much natural wealth that can be used to support the life of the country and its people, one of the natural wealth owned is in the tourism sector. Poso City as part of Indonesia has so much natural beauty, but the human tragedy that has occurred in Poso, leaves a very dark story, even has an impact on the memory of all Poso people, as well as people outside poso. This impact is obviously traumatizing for the Poso community, the conflict inflicts a deep and lasting trauma even though it has long passed. This research is very important to be carried out in Poso, not only because the issue of tourism is a hot topic for now and its relation to the image of the city of Poso (challenges and opportunities), but also just to bring to the surface the old story of the tragedy that has occurred, which then directs the research to identify the attitudes and traumas of tourism and tourists. But most important in the study is how researchers try to put tourism as a trauma recovery